Identification of key genes and signaling pathways of liver cancer and model construction for prognosis and diagnosis based on bioinformatics analysis - Benzun Wei; Yao Zheng; Shuaijun Yu; Aiyun Wang; Xiao Lyu (PLoS ONE, 2025)
Objective This study aims to identify key genes, biomarkers, and associated signaling pathways involved in liver cancer progression by analyzing differentially expressed genes (DEGs) between normal and cancerous liver tissues, with the goal of establishing diagnostic and prognostic models for liver cancer. Methods Two datasets, GSE39791 and GSE84402 from GEO, and clinical data from TCGA were selected. Differentially expressed genes (DEGs) were identified using the “limma” package in R, and volcano plots were generated. Functional enrichment of DEGs was performed with Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis. Logistic regression and multivariate Cox regression models were established for diagnostic and prognostic prediction. The immortalized liver cell line THLE-3 and HepG2 cells were used to verify key gene expression via RT-qPCR and Western blot. HepG2 cells were transfected to up- and down-regulate SNAPC2 expression, and cell proliferation, migration, and apoptosis were assessed using CCK-8, colony formation, scratch, transwell migration assays, and flow cytometry with Annexin V-PE/7-AAD staining. Additionally, Gene Set Enrichment Analysis (GSEA) of SNAPC2 revealed its involvement in cancer-related pathways. Results Bioinformatics analysis identified 10,961 down-regulated and 3,321 up-regulated genes in the GSE39791 and GSE84402 datasets, and 272 down-regulated and 4,855 up-regulated genes in TCGA data. GO and KEGG analysis revealed 3,820 co-DEGs associated with processes like cell differentiation and morphogenesis. CDCA8, GRPEL2, HAVCR1, MT3, MYCN, NDRG1, PHOSPHO2, SNAPC2, SOCS2, and TXNRD1 were selected to construct prognostic models, and MYCN, NDRG1, TXNRD1, SNAPC2, PHOSPHO2, and CDCA8 for diagnostic models. Western blot validation showed upregulation of CDCA8, GRPEL2, HAVCR1, MYCN, NDRG1, PHOSPHO2, SNAPC2, and TXNRD1 in liver cancer tissues, correlating with poor prognosis. Moreover, reduced SNAPC2 expression in HepG2 cells led to decreased proliferation and migration, and increased apoptosis, suggesting SNAPC2 plays a role in liver cancer progression by promoting cell proliferation and migration. Conclusion CDCA8, GRPEL2, HAVCR1, MT3, MYCN, NDRG1, PHOSPHO2, SNAPC2, SOCS2, TXNRD1 were key genes for liver cancer prognosis and diagnosis. Moreover, lowering SNAPC2 expression could improve the prognosis of liver cancer through decreasing proliferation and migration s and increasing apoptosis of cancer cell.